Letter (copy) : Foodstuffs for Spain - Citrine, Walter, 1887-1983
029-0108-001 9513/ST/JEM. WMC/FC/EK/1311 Secretary's. 20th July, 1937. Mr. E. Winstanley, The Co-operative Wholesale Society Limited, Export Department, 1, Balloon Street, Manchester 4. Dear Mr. Winstanley, FOODSTUFFS FOR SPAIN. Many thanks for your letter or the 16th instant stating that you have available a special line of two hundred cases of Sweetened Condensed Milk which you are prepared to clear at the special price of 20/- per case. We are bearing this offer in mind and will communicate with you again in due course on this matter. Yours sincerely, General Secretary. 292/946/29/108